Antimicrobial Activity of Essential Oils and Herbal Extracts Against Etiological Agent of Dental Caries. Issue 7 (2nd October 2016) - Besra, Mamta; Kumar, Vipin
Abstract: Dental caries is one of the most prevalent diseases in humans which cause irreversible damage to the teeth. Plaque formation is the main cause of dental caries occurrence in human. Dental plaque is formed by the colonization and accumulation of oral cariogenic pathogens. The study aimed to emphasize the antimicrobial potency of herbal essential oils and other bioactive compounds against dental caries pathogens. In addition, there is a great demand to investigate potent traditional herbal formulation to inhibit the plaque formation to lower the risk of tooth loss. The study revealed that, essential oils and herbal extracts are considerably effective against cariogenic pathogens. The Streptococcus mutans has been implicated as a major etiological agent of dental caries, Streptococcus genus is always the foundation of dental plaque as they exhibit intergeneric co-aggregation. Most treatments are now aimed at either elimination of this bacterium or suppression of its virulence. Herbal alternatives are economic and ecofriendly, simultaneously alleviating many of the side effect that are often connected with synthetic antimicrobial agents.